Internalisasi Budaya Senyum, Sapa, Salam, Sopan, Santun (5S) dalam Pola Kepemimpinan Kiai untuk Membentuk Budaya Ta’ẓīm Santri - Ardian, Yudi; Arrozi, Fatahillah; Aftori, Rohmatika (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2021)
The weakening of the ta'dzim culture of santri towards kiai in Islamic boarding schools becomes a separate urgency to conduct research on the leadership pattern of kiai. The purpose of this study was to find out how kiai integrate local wisdom (smile, greeting, regards, polite, courteous) in their leadership patterns to form a culture of ta'ẓīm among students in Islamic boarding schools. This research uses a qualitative approach with a case study design. The research site at Al-Ishlah Bondowoso Islamic Boarding School, which is located at Jl. Jember 17-19 Dadapan Grujugan Bondowoso. The sample, hereinafter referred to as the resource person was determined by using a purposive sampling technique, which deemed to meet the criteria as a theoretical sample. The data collection technique carried out in three stages: interviews, participant observation, and documentation. Furthermore, the data will be analyzed using taxonomic analysis techniques. The findings in this study are that kiai integrate local wisdom, namely the culture of smiling, greeting, regards, polite and courteous in their behavior. So that the culture is embedded in his personality and becomes a characteristic in his strong leadership pattern to form a culture of ta'ẓīm santri.